Reversal of chemotherapy resistance in gastric cancer with traditional Chinese medicine as sensitizer: potential mechanism of action - Zhou, Chencong; Wu, Kaihan; Gu, Meng; Yang, Yushang; Tu, Jiatao; Huang, Xuan (Frontiers in Oncology, 2025)
Gastric cancer (GC) remains one of the most common types of cancer, ranking fifth among cancer-related deaths worldwide. Chemotherapy is an effective treatment for advanced GC. However, the development of chemotherapy resistance, which involves the malfunction of several signaling pathways and is the consequence of numerous variables interacting, seriously affects patient treatment and leads to poor clinical outcomes. Therefore, in order to treat GC, it is imperative to find novel medications that will increase chemotherapy sensitivity and reverse chemotherapy resistance. Traditional Chinese medicine (TCM) has been extensively researched as an adjuvant medication in recent years. It has been shown to have anticancer benefits and to be crucial in enhancing chemotherapy sensitivity and reducing chemotherapy resistance. Given this, the mechanism of treatment resistance in GC is summed up in this work. The theoretical foundation for TCM as a sensitizer in adjuvant treatment of GC is established by introducing the primary signal pathways and possible targets implicated in improving chemotherapy sensitivity and reversing chemotherapy resistance of GC by TCM and active ingredients.